Of birds, guano, and man: William Vogt's "Road to Survival". - Mccormick, Maureen A. (My University, 2005)
William Vogt's best-selling and influential neo-Malthusian text Road to Survival articulated the conservation sensibility of his day and was literally read around the world. Vogt (1902--1968) came to his conclusions about land-use and population control through ecological research, confirming that conservation approach of natural resources would come by managing human behavior, rather than by directing the behavior of non-human organisms. Human behavior had indeed crossed into the realm of the natural sciences in so far as conservation was concerned. Specifically, Vogt urged humans to adopt population control to circumscribe land use.

Vogt was one of a group of ecologists who claimed that humans must adapt to their environment, albeit an environment they were capable of altering; Frank Fraser Darling, Julian Huxley, and Fairfield Osborn joined him. Vogt called for population control to become part of United States foreign policy, as would happen in the 1960s. He assigns ecologists to the role of expert policy advisor in a democratic society; he wants individuals to voluntarily choose to limit family size but is prepared to demand coercion. Vogt's work has long been seen as an early example of a land-use sensibility associated with the modern environmental movement; in reality it reflects an intermediate stage between Progressive Era conservation and the late twentieth-century environmental concerns for quality of life. Finally, Vogt's ideas have real life consequences. He was influential in the origins of what is now the World Conservation Union, which in its earliest stages as the International Union for the Protection of Nature recommended The Road to Survival and he was national director of Planned Parenthood Federation of America, the leading voice for birth control in the United States.
Road to survival.
Keywords: Vogt, William, 1902-1968; History of Science.; History, United States.; Birth control.; Conservation of natural resources.